Iranian Scripts for Aramaic Languages: The Origin of the Mandaic Script - Häberl, Charles G. (Bulletin of ASOR, 2006)
The unique cursive script still employed by the Mandaeans of Iraq and Iran, which is unlike any other script found in the modern Middle East, may provide a clue to the obscure origins of their written literature and their emergence as a distinct religious tradition. Comparison with ancient scripts from the regions where the Mandaeans are found today indicates that the Mandaic script is a product of the late Parthian period (and more specifically the second century C.E.) and has its closest affinities with a group of scripts ranging from Anatolia and the Caucasus in the north to Characene and Elymais in the south, all of which appear to derive from or to be heavily influenced by the Parthian chancery script. The association of the Mandaeans with the later Arsacids is corroborated by their own legends and their textual tradition.